E-Bisnis Dan Problematika Dunia Kerja Di Masa Pandemi Covid-19 - Abdullah Sani Kurniadinata (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
The Covid-19 Pandemic period that has lasted so far has had a huge impact on various sectors. It’s including the education, politics, economy and tourism sectors as well as others. It’s relationship with Workers Civil Rights has an impact on the amount of financial income, or even to dismissal (Termination of Employment). Meanwhile, before the Covid-19 outbreak, the world of work also left specific problems related to workers' rights, whether it was related to wages, security, health and even justice issues which were always demanded due to conflicts of different interests. Entrepreneurs on the one hand understand justice according to their side's view, and workers also view justice according to their version. In the current situation and conditions, e-business is a solution to continue to support business in order to continue to exist, aspecially B2C (Bussines to Consument). E-business is a business activity that is carried out automatically by utilizing computer networks and internet technology. E-Business today (during the Covid-19 pandemic) plays a very important role in supporting the economy and micro-businesses in the community. Therefore, the authors try to use an economic, social and legal approach in this study. Keywords: E-Business, Covid-19, Workers